2005
DOI: 10.1007/s00247-005-1462-2
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric lymph nodes in children: what is normal?

Abstract: MLN with a short-axis diameter of >5-10 mm are commonly found on abdominal CT examination of children with a low likelihood for mesenteric lymphadenopathy and should be considered a non-specific finding. A short-axis diameter of 8 mm might better define the upper limit of normal mesenteric lymph node size in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 7 publications
4
42
0
3
Order By: Relevance
“…All examinations were performed on a Logos Hi-Vision C machine (Hitachi Medical Systems, Tokyo, Japan) using a broadband convex transducer (frequency 3.5–5 mHz) for the first evaluation and then a microconvex transducer (frequency 4–8 mHz) for a detailed evaluation of the bowel, lymph nodes, and mesentery. The following ultrasound parameters were evaluated: bowel wall thickness (normal ≤2 mm),18 small bowel dilatation (normal <25 mm),19 free fluid within the peritoneal cavity, enlarged mesenteric lymph nodes (short axis >8 mm),20 enlarged vermiform appendix (diameter >6 mm), and mesenteric hypertrophy (presence of hyperechoic area around thickened bowel wall >5 mm) 21,22. All patients were examined in the morning after fasting for at least 6 hours with an empty or moderately replete bladder.…”
Section: Methodsmentioning
confidence: 99%
“…All examinations were performed on a Logos Hi-Vision C machine (Hitachi Medical Systems, Tokyo, Japan) using a broadband convex transducer (frequency 3.5–5 mHz) for the first evaluation and then a microconvex transducer (frequency 4–8 mHz) for a detailed evaluation of the bowel, lymph nodes, and mesentery. The following ultrasound parameters were evaluated: bowel wall thickness (normal ≤2 mm),18 small bowel dilatation (normal <25 mm),19 free fluid within the peritoneal cavity, enlarged mesenteric lymph nodes (short axis >8 mm),20 enlarged vermiform appendix (diameter >6 mm), and mesenteric hypertrophy (presence of hyperechoic area around thickened bowel wall >5 mm) 21,22. All patients were examined in the morning after fasting for at least 6 hours with an empty or moderately replete bladder.…”
Section: Methodsmentioning
confidence: 99%
“…65 Because normal children have been shown to have lymphadenopathy up to 5 mm, the authors recommend noting only lymphadenopathy greater than 1 cm unless there is clear central necrosis on CT, calcification, or low signal intensity on T2-weighted MRI images.…”
Section: Lymphadenopathy: What Size Is Abnormal?mentioning
confidence: 99%
“…Several authors have studied the normal dimensions of abdominal lymph nodes at imaging studies of adult individuals in different clinical conditions, but few studies with children are found in the literature (3,5) . A criterion that is frequently utilized to define lymph node enlargement is the smallest diameter > 4 mm (measured by means of ultrasonography) or 5 mm (CT) (14)(15)(16)(17) . However, enlarged lymph nodes are found on imaging studies of asymptomatic patients, with these same values (14,(18)(19)(20) .…”
Section: Discussionmentioning
confidence: 99%